Architecture from '[Les Cathédrales de France. [With plates.]]'. - Auteur inconnu... (The British Library, 1861)
Notice issue d Europeana. This image has been taken from scan 000227 from "[Les Cathedrales de France. [With plates.]]". The title and subject terms of this image have been generated from tags, created by users of the British Library's flickr photostream.
http://creativecommons.org/publicdomain/mark/1.0/
Keywords: europeana; image; patrimoine europeen; Bibliothèque numerique; iconographie